IMPLIKASI TEORI ARBITRAGE PRICING THEORY PADA RETURN SAHAM PERTAMBANGAN PT ANTAM TBK - Aini, Nur Syahidah Qurotu; Muhammad Husaini; Dian Fajarini (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This research aimed to analyze the effect of microeconomic and macroeconomic factors on stock returns of PT Aneka Tambang Tbk. Stock returns here refer to changes in stock prices that reflect the profits or losses received by investors in a certain period of time. The variables studied include stock trading volume, world gold prices, exchange rates, GDP, and interest rates. The method used is a quantitative approach with secondary data in the form of quarterly time series for the period January 2008-December 2023. The results show that in the short term, interest rates have a negative and significant effect on stock returns. On the other hand, in the long run, trading volume and GDP have a significant negative effect, while global gold prices have a significant positive effect.